2016
DOI: 10.5430/cns.v4n3p39
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childbirth preparation courses on anxiety and self-efficacy in coping with childbirth

Abstract: Objective: To evaluate the effect of childbirth preparation courses on anxiety and self-efficacy levels in coping with childbirth. Methods: A study was conducted on a convenience sample of nulliparous women. The intervention groups consisted of 31 women who attended a 5-week childbirth preparation course and 39 women who attended a 2-week course. A control group included 32 women who did not attend any of the childbirth preparation courses. Levels of anxiety and self-efficacy were measured before and after chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In this study, depression, anxiety, and stress symptoms were found to be lower in both prenatal and postnatal periods of the women receiving antenatal education compared to the control group. Previous studies have reported that women attending training courses showed less anxiety symptoms (Ip et al, 2009;Khaikin et al, 2016). The information pregnant women received during pregnancy was reported to reduce birth anxiety in a qualitative study (Miquelutti et al, 2013b).…”
Section: Discussion Of Depression Anxiety and Stress Symptoms Of The Groups Before And After Antenatal Educationmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, depression, anxiety, and stress symptoms were found to be lower in both prenatal and postnatal periods of the women receiving antenatal education compared to the control group. Previous studies have reported that women attending training courses showed less anxiety symptoms (Ip et al, 2009;Khaikin et al, 2016). The information pregnant women received during pregnancy was reported to reduce birth anxiety in a qualitative study (Miquelutti et al, 2013b).…”
Section: Discussion Of Depression Anxiety and Stress Symptoms Of The Groups Before And After Antenatal Educationmentioning
confidence: 91%
“…There was a significant negative correlation of anxiety level with childbirth self-efficacy, and also between the ways of coping with the delivery process and the severity of birth pain (Beebe et al, 2007). Furthermore, women attending prenatal education programs have been reported to be experiencing less birth anxiety, stress, and depression (Ip et al, 2009;Khaikin et al, 2016;Miquelutti et al, 2013a). Byrne et al (2014) found in a single-group experimental study that depression scores of the pregnant women decreased after the education they received and the anxiety and stress scores of the same pregnant women were very low in the postpartum period.…”
Section: Birth Self-efficacy Depression Anxiety and Stressmentioning
confidence: 99%
“…The current study deals with a unique population of primigravid women in the ultra-orthodox religious Jewish community of Israel. The literature showed that fear of childbirth was associated with reduced maternal confidence [ 1 , 2 , 3 ], increasing anxiety, and reduced self-efficacy [ 5 , 8 ]. The aim of the present study was to examine the contribution of childbirth preparation courses to a woman’s ability to cope successfully with childbirth by raising her self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of childbirth, women with high levels of anxiety tend to opt for an epidural injection as compared to women with low fear levels [ 4 , 5 ]. Self-efficacy was defined by Lowe (1993) as one’s belief of the ability to perform a behavior successfully in a particular context [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation